PEMBINAAN KESENIAN KETHOPRAK DI DESA KEMLOKO, KECAMATAN KRANGGAN, KABUPATEN TEMANGGUNG, PROVINSI JAWA TENGAH - Endang Retnaningdyah Elis Noviati Mariani (Abdi Seni, 2020)
Kethoprak performances have begun to fade along with the development of culture that is increasingly entering Indonesia. In preserving the art of kethoprak, stage arrangements, costume costumes, performance management, and so on can be done. In addition, there are also ways that promotion can not be efficiently so that it is less well known in the outside community. The method used in this PPM activity by using a model approach to various parties or to the personal. Various approaches that can be developed in PPM activities include Personal Approach, Group Approach, Social Approach, Educational Approach, and Discussion method. Art that has begun to be marginalized was reappointed for guidance in a number of fields including kethoprak which is the main focus. In addition there are several other arts such as musical art, song macapat, jaran kang, dance, art also revived again. The training management needs to be reorganized so that it can run routinely. Similarly, human resources must also be regenerated so that there is a replacement.Keywords: Art, Kethoprak, Kranggan.